Zjawiska niecodzienne, klęski elementarne i przemarsze wojsk w Wielkopolsce w XVII i XVIII w. i ich wpływ na funkcjonowanie klasztoru benedyktynek w Poznaniu w świetle Kronik Benedyktynek Poznańskich - Lewandowska, Ada (Saeculum Christianum. Pismo Historyczne, 2018)
The Monastery in Poznań was founded in 1607 by Magdalena Mortęska – the reformer of the Benedictine Order. By analysing the monastic cornicles, the author wanted to show the influence of extra-ordinary events in Greater Poland and Poznan in 17th and 18th Century on life of enclosed nuns. The article describes what changed when people visited the monastery, what life of nuns looked like during epidemics, floods and other disasters that took place in Greater Poland. The influence of wars and quartering foreign armies in the city of Poznan on life of nuns in the Benedictine Monastery was also included.